Compromised regulation of the rat brain parenchymal arterioles in vasopressin‐associated acute hyponatremia. (14th July 2020) - Aleksandrowicz, Marta; Kozniewska, Ewa
Abstract: Objective: In this study, we examined the effect of acute hyponatremia associated with vasopressin (AVP) on the responses of the isolated rat's MCAs and PAs to acidosis, nitric oxide donor (SNAP) and to endothelium‐dependent vasodilator ATP. Methods: The studies were performed on isolated, perfused and pressurized MCAs and PAs in control conditions and during AVP‐associated hyponatremia. Hyponatremia was induced in vitro by lowering Na + concentration from 144 to 121 mmol/L in intra‐ and extravascular fluid in the presence of AVP. Results: Parenchymal arterioles showed greater response to an increase in H + and K + ions concentration and to ATP in comparison with MCAs in control normonatremic conditions. Both PAs and MCAs constricted in response to acute hyponatremia associated with AVP. Interestingly, disordered regulation of vascular tone was observed in PAs but not in MCAs. The abnormalities in the regulation comprised a significant reduction of PA response to acidosis and the absence of the response to the administration of SNAP or ATP. Conclusions: Arginine vasopressin‐associated hyponatremia leads to constriction and dysregulation of PAs which may impair neurovascular coupling.